A comparison of route-choice navigation across air pollution exposure, CO2 emission and traditional travel cost factors. (December 2018) - Alam, M.S.; Perugu, H.; McNabola, A.
Highlights: Air pollution dose as a route choice factor is compared to traditional cost factors. The lowest air pollution dose route was significantly different to other routes. Traditional cost factors resulted in a series of similar routes with overlapping. Small reductions in travel time resulted in large increases in dose. Small reductions in dose resulted in small increase in travel time. Abstract: The present investigation examines the contrast between traditional travel cost factors and personal exposure to PM10, in optimum route choice selections. A land use regression model was applied to Dublin city to enable prediction of PM10 at route level throughout the city. This exposure data enabled the comparison of optimum route choice for lowest: travel time, distance, running cost, generalised cost, CO2 emission and air pollution dose. The results showed that lowest travel time and distance routes did not offer the lowest dose, and routing decisions based on time, distances and related parameters were most contradictory with the dose based routing exercise. When the lowest dose routes were compared against shortest routes, the lowest dose route only caused a small increase (<2%) in these values costing a small saving from dose (<3.8%). However, when routes were based on lowest CO2, the small decrease in CO2 values led to a large increase in dose (+12.8%). Route choice based on shortest time, distance or CO2 were all based on inter-related factors and similar routes for these three objective functions were found. Route choice based on air pollution dose was related to the length of time taken and the degree of congestion, but also to many other factors which impacted on the dispersion of emissions but not necessarily on the emission rate or quantity themselves. Therefore the optimum route choices for least dose were significantly different to the other cost factors.